PTU-290 What's on offer for patients presenting to a giant (gi and nutrition team) clinic in a specialist cancer centre?. (22nd June 2015) - Muls, A; Lalji, A; Andreyev, H
Abstract : Introduction: GI toxicity experienced by patients related to cancer therapy has been largely ignored by gastroenterologists. Method: A prospective evaluation was conducted of patients referred with chronic changes in GI function after cancer therapy after discharge from our clinic. All patients complete a Gastrointestinal Symptom Rating Scale recording 30 symptoms and a Bristol Stool Chart at every clinic visit. Patient characteristics, symptom incidence, severity, investigations and diagnoses were recorded. Results: From April 2013 to March 2014, there were 1266 clinic appointments, 398 new patients and 868 follow-ups, 326 patients were discharged. 62% referred by in-house oncology teams, 24% tertiary and 14% GP referrals. Median age was 68 years (20–90), the majority were male (56%). Time from cancer diagnosis to referral was 3.3 years (median, range 0–42). The majority were treated for urology (43%) or gynaecological malignancy (21%), 12% for colorectal, 10% for GI and 14% for other cancers. 94% had more than one troublesome symptom. The most commonly reported GI symptoms (diarrhoea, urgency, flatulence, tenesmus, bloating, abdominal pain, faecal incontinence, borborygmi, nocturnal defaecation, perianal pain and steatorrhoea) all improved by discharge. Only 4% had symptoms that required only endoscopic investigation. 84% reported ongoing fatigue, 45% urinary and 36% sexual concerns. Following an algorithm proven to be effective, 86% required blood tests, 58% OGD+ duodenal aspirate, 53% breath tests, 51% SeHCAT scanning, 48% flexible sigmoidoscopy, 20% colonoscopy, 45% stool faecal elastase and 3% other radiological imaging. Six investigations (median 0–10) were requested. 62% had 3 or more diagnoses made which included 46% small bowel bacterial overgrowth, 38% vitamin D deficiency, bile acid malabsorption 28%, gastritis 22%, radiation-induced bleeding 20%, vitamin B12 deficiency 17%, weak pelvic floor 17%, 13% had polyp requiring removal, 5% pancreatic insufficiency. 3 visits were required (median, 1–16) before discharge. Those requiring more than 1 visit (n = 256) were followed up for 6 months (median, 0.4–142 months). 36% were referred for dietetic assessment and targeted dietary interventions as part of management. Referrals to other teams included: psychological support (4%), urology (2%), psychosexual counselling (1%), physiotherapy (1%) and endocrinology (1%). Conclusion: Many GI causes contribute to chronic change in bowel function after cancer treatment, endoscopic evaluation without addressing other GI symptoms is only appropriate in a small minority. Most can be discharged after a small number of consultations with significant improvement or resolution of symptoms if a systematic investigational and treatment approach is adopted. Disclosure of interest: None Declared.